Developing the Composition Skills of English as a Foreign Language Learners through Blended Learning - DAKHMOUCHE, Linda (Journal of Human Sciences, 2018)
Innovation and development in the sector of information and communication technologies have significantly impacted the field of education by offering new possibilities for learning and teaching, particularly in English Language Teaching. Dissatisfaction with the traditional teaching of writing and with e-learning has led to the emergence of a new instructional paradigm called blended learning. This paradigm has become very popular in many foreign countries, and more specifically in the Arab world. The purpose of this study is to investigate the effectiveness of blended learning in developing the composition skills of English as Foreign Language university students in an Algerian context. For this purpose, a quasi-experiment and an evaluation questionnaire are used as data collection tools. On the basis of the results obtained, some recommendations are provided.